Developing Government Employee’s Competence through Education at the Regional Hospital of Biak, Papua - Fatmawada S; M. Saleh Laha; Iswahyudi Iswahyudi; Karina Arfany Arfah (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
This study uses a descriptive method with a qualitative approach, which aims to analyze the development of the competence of government employees through education at the Regional Hospital of Biak, Papua Province. The results showed that the development of the competence of government employees through education has been running. However, it is still not optimal and there is still a need for development so that the government employees can have theoretical, conceptual, professional, productive, responsible, and moral capabilities both in carrying out their duties and functions. Through an appropriate equitable development strategy and being able to meet the agency's strategic plan as well as the needs for the government employees' job competency standards and career development. Motivation from the leadership is also one of the factors affecting the competence of the government employees